Temperature monitoring of nonanaesthetised patients in a cardiac catheterisation laboratory. Issue 11 (15th April 2016) - Kennedy, Wendy; Conway, Aaron
Abstract : Aim and objectives: To identify the prevalence that temperature reduced by more than 1 °C from pre‐ to post‐procedure in a sample of non‐anaesthetised patients undergoing procedures in a cardiac catheterisation laboratory. Background: Advances in medical technology are minimising the invasiveness of diagnostic tests and treatments for disease, which is correspondingly increasing the number of medical procedures performed without sedation or anaesthesia. Procedural areas in which medical procedures are performed without anaesthesia are typically kept at a cool temperature for staff comfort. As such, there is a need to inform nursing practices with regard to the thermal management of non‐anaesthetised patients undergoing procedures in surgical or procedural environments. Design: Single‐site observational study. Methods: Patients were included if they had undergone an elective procedure without sedation or anaesthesia in a cardiac catheterisation laboratory. Ambient room temperature was maintained between 18 and 20 °C. Passive warming with heated cotton blankets was applied. Nurses measured body temperature and thermal comfort before and after 342 procedures. Results: Mean change in temperature was −0.08 °C (Standard deviation 0.43). The reduction in temperature was more than 1 °C after 11 procedures (3.2%). One patient whose temperature had reduced more than 1 °C after their procedure reported thermal discomfort. A total of 12 patients were observed to be shivering post‐procedure (3.6%). No demographic or clinical characteristics were associated with reduction in temperature of more than 1 °C from pre to post‐procedure. Conclusions: Significant reduction in body temperature was rare in our sample of non‐anaesthetised patients. Relevance to clinical practice: Similar results would likely be found in other procedural contexts during procedures conducted in settings with comparable room temperatures where passive warming can also be applied with limited skin exposure.